Application of CPLD in Microcomputer-based Protection Device for Power System - WEN Yang-dong; FAN Jun-hua; YU Mao-qua (Gong-kuang zidonghua, 2011)
For problems of few expandable IO of DSP and complex circuit design of microcomputer-based protection device for power system by use of DSP and single chip microcomputer, CPLD chip EPM7128 was used to design logic circuits of expanded digital IO, handshaking signal, data communication, and frequency measurement of the device, and design and implementation of CPLD in communication between dual CPUs were introduced emphatically. The simulation result verified correctness of the CPLD logic circuits. The application of the circuits in the microcomputer-based protection device also showed their flexibility and stability.